Statistical Analysis of Awareness of Other Sexually Transmitted Infections In Relation to Human Immunodeficiency Virus - Bodunwa, O. K.; Fatunsi, R. F. (Journal of Science, Technology and Innovation Research, 2025)
We studied statistical analysis of the level of awareness on Sexually Transmitted Infections (STIs) in relation Human Immunodeficiency Virus (HIV) across Nigeria utilizing data from the 2018 Demographic and Health Survey (DHS). From the study, variables that influenced the level of awareness were identified and the relationship between these variables was determined using Chi-square and logistic regression model. From the results, it was revealed that there is significant differences in STI awareness compared to HIV knowledge. Urban residents, people with higher education, and older populations showed greater awareness of STIs. There is a strong correlation between HIV and STI awareness implying that increased in the knowledge of HIV could potentially enhance awareness of other STIs. Individuals who were aware of HIV were nearly twice as likely to be informed about other STIs, underscoring the benefits of integrated sexual health education programs. Northern Nigeria exhibiting lower STI awareness compared to the southern regions. This geographical variation pointed to the necessity for region-specific public health strategies to bridge the awareness gap and ensure equitable access to sexual health information nationwide. Conclusively, more effort is required to boost STI awareness among rural and less educated populations through targeted, region-based in Nigeria.